Dealing with Crucial Aspects of Action Research - Sharma, Lok Raj (International Research Journal of MMC, 2022)
Action research, which is a dynamic iterative process, is a deliberate and solution-oriented investigation accomplished collectively or personally in order to solve an existing problem. It entails the participants who scrutinize their own instructive practice systematically and cautiously. It is characterized by spiraling cycles of problem identification, systematic data collection, reflection, analysis, actions taken based on data, and finally problem redefinition. It is an applied form of inquiry useful in divergent situations. It involves such people who keep working to improve their performances, skills, strategies and techniques. The prime objective of this article is to deal with the crucial aspects of action research, such as definitions of action research, field of action research, process, steps, principals, characteristics, benefits and demerits of action research. This article has been prepared on the basis of secondary data gathered from research books and journal articles. It is useful especially to the researchers, because it focuses on the indispensable aspects of action research, and it is undoubtedly necessary for them to have basic ideas about its underlying facets to carry out action researches in their real life situations.